Enzymatic degradation behavior and cytocompatibility of silk fibroin–starch–chitosan conjugate membranes - Baran, E. T. (2012)
The objective of this study was to investigate the influence of silk fibroin and oxidized starch conjugation on the enzymatic degradation behavior and the cytocompatability of chitosan based biomaterials. The tensile stress of conjugate membranes, which was at 50 Megapascal (MPa) for the lowest fibroin and starch composition (10 weight percent (wt.%)), was decreased significantly with the increased content of fibroin and starch. The weight loss of conjugates in α-amylase was more notable when the starch concentration was the highest at 30 wt.%. The conjugates were resistant to the degradation by protease and lysozyme except for the conjugates with the lowest starch concentration. After 10 days of cell culture, the proliferation of osteoblast-like cells (SaOS-2) was stimulated significantly by higher fibroin compositions and the DNA synthesis on the conjugate with the highest fibroin (30 wt.%) was about two times more compared to the native chitosan. The light microscopy and the image analysis results showed that the cell area and the lengths were decreased significantly with higher fibroin/chitosan ratio. The study proved that the conjugation of fibroin and starch with the chitosan based biomaterials by the use of non-toxic reductive alkylation crosslinking significantly improved the cytocompatibility and modulated the biodegradation, respectively.